Crisis Communication About the Maui Wildfires on TikTok: Content Analysis of Engagement With Maui Wildfire–Related Posts Over 1 Year - Jim P Stimpson; Aditi Srivastava; Ketan Tamirisa; Joseph Keaweʻaimoku Kaholokula; Alexander N Ortega (JMIR Formative Research)
Abstract BackgroundThe August 2023 wildfire in the town of Lāhainā on the island of Maui in Hawaiʻi caused catastrophic damage, affecting thousands of residents, and killing 102 people. Social media platforms, particularly TikTok, have become essential tools for crisis communication during disasters, providing real-time crisis updates, mobilizing relief efforts, and addressing misinformation. Understanding how disaster-related content is disseminated and engaged with on these platforms can inform strategies for improving emergency communication and community resilience. ObjectiveGuided by Social-Mediated Crisis Communication theory, this study examined TikTok posts related to the Maui wildfires to assess content themes, public engagement, and the effectiveness of social media in disseminating disaster-related information. MethodsTikTok posts related to the Maui wildfires were collected from August 8, 2023, to August 9, 2024. Using TikTok’s search functionality, we identified and reviewed public posts that contained relevant hashtags. Posts were categorized into 3 periods: during the disaster (August 8 to August 31, 2023), the immediate aftermath (September 1 to December 31, 2023), and the long-term recovery (January 1 to August 9, 2024). Two researchers independently coded the posts into thematic categories, achieving an interrater reliability of 87%. Engagement metrics (likes and shares) were analyzed to assess public interaction with different themes. Multivariable linear regression models were used to examine the associations between log-transformed likes and shares and independent variables, including time intervals, video length, the inclusion of music or effects, content themes, and hashtags. ResultsA total of 275 TikTok posts were included in the analysis. Most posts (132/275, 48%) occurred in the immediate aftermath, while 76 (27.6%) were posted during the long-term recovery phase, and 24.4% (n=67) were posted during the event. Posts during the event garnered the highest average number of likes (mean 75,092, SD 252,759) and shares (mean 10,928, SD 55,308). Posts focused on “Impact & Damage” accounted for the highest engagement, representing 36.8% (4,090,574/11,104,031) of total likes and 61.2% (724,848/1,184,049) of total shares. “Tourism Impact” (2,172,991/11,104,031, 19.6% of likes; 81,372/1,184,049, 6.9% of shares) and “Relief Efforts” (509,855/11,104,031, 4.6% of likes; 52,587/1,184,049, 4.4% of shares) were also prominent themes. Regression analyses revealed that videos with “Misinformation & Fake News” themes had the highest engagement per post, with a 4.55 coefficient for log-shares (95% CI 2.44-6.65), while videos about “Tourism Impact” and “Relief Efforts” also showed strong engagement (coefficients for log-likes: 2.55 and 1.76, respectively). ConclusionsTikTok is an influential tool for disaster communication, amplifying both critical disaster updates and misinformation, highlighting the need for strategic content moderation and evidence-based messaging to enhance the platform’s role in crisis response. Public health officials, emergency responders, and policy makers can leverage TikTok’s engagement patterns to optimize communication strategies, improve real-time risk messaging, and support long-term community resilience.